Respostas
respondido por:
2
a) 2x² - 128 = 0
2x^2 = 128
x^2 = 128/2
x^2 = 64
x = +- √ 64
x = +- 8
S = { 8 ; - 8 }
a) x ² + 8x + 12 = 0
x = - 8 +- 4/2
x' = - 2
x" = - 6
S = { - 2 ; - 6 }
2x^2 = 128
x^2 = 128/2
x^2 = 64
x = +- √ 64
x = +- 8
S = { 8 ; - 8 }
a) x ² + 8x + 12 = 0
x = - 8 +- 4/2
x' = - 2
x" = - 6
S = { - 2 ; - 6 }
topzinhos:
Muito Obrigada :)
respondido por:
1
a) 2x^2-128=0
2x^2=0+128
2x^2=128
x^2=128/2
x^2=64
x= raiz de 64
x=-/+8
b) x^2+8x+12=0
delta=b^2-4ac
delta=8^2-4.1.12
delta=64-48
delta=16
x=-b-/+ raiz de delta/2a
x=-8-4/2.1
x=-12/2
x=-6
x=-8+4/2.1
x=-4/2
x=-2
2x^2=0+128
2x^2=128
x^2=128/2
x^2=64
x= raiz de 64
x=-/+8
b) x^2+8x+12=0
delta=b^2-4ac
delta=8^2-4.1.12
delta=64-48
delta=16
x=-b-/+ raiz de delta/2a
x=-8-4/2.1
x=-12/2
x=-6
x=-8+4/2.1
x=-4/2
x=-2
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás